How did that individual make that perceptual decision?. (27th December 2018) - Booth, David A.
Abstract: Suboptimality of decision making needs no explanation. High-level accounts of suboptimality in diverse tasks cannot add up to a mechanistic theory of perceptual decision making. Mental processes operate on the contents of information brought by the experimenter and the participant to the task, not on the amount of information in the stimuli without regard to physical and social context.